Contrasting practices and perceptions of urban agriculture in Portugal - Cecília Delgado (International Journal of Urban Sustainable Development, 2018)
This paper presents a conceptual exploration of Urban Agriculture in Portugal. We argue that Portuguese Urban Agriculture primarily focuses on food production for self-consumption and that its links with the other components of urban as a system are quite limited. To substantiate our argument several Urban Agriculture international definitions are presented and critically analysed along with: 1) interviews of relevant key actors; and, 2) a web search based on key words. We conclude that there is a need to clarify the very concept of Urban Agriculture among actors involved. This could be achieved through a national network able to raise a must needed debate about this promising sector. Political decision makers, civil society, and planners, among others should be involved in this collaborative process. Finally, the paper brings some reflections on what the Portuguese experience contributes to the broader debate and definitions of Urban Agriculture.